Immune Response in Mice Immunized with Chimeric H1 Antigens - Kotey, Erasmus Nikoi; Ampofo, William Kwabena; Daines, Rebecca (MDPI, 2021)
: Identification of a universal influenza vaccine candidate has remained a global challenge for both humans and animals. This study describes an approach that uses consensus sequence building to generate chimeric HAs (cHAs): two resultant H1 HA-based chimeras comprising of conserved sequences (within several areas spanning the head and stalk regions) of H1 and H5 or H9 HAs. These cHAs expressed in Drosophila cells (S2) were used to immunize mice. All immunized mice were protected from an infectious H1 virus challenge. Seroconverted mice sera to the H1 cHAs inhibited both the challenge virus and an H5 virus isolate by haemagglutination inhibition (HI) assay. These findings further emphasize that cHAs induce cross-reactive antibodies against conserved areas of both head and stalk regions of the seasonal influenza A (H1N1) pdm09 virus’ HA and holds potential for further development of a universal influenza vaccine.
Keywords: universal influenza vaccine; broad-reactive antibodies; chimeric haemagglutinin; therapeutic; prophylactic; seasonal influenza; cross-reactivity; Jean-Remy Sadeyen; Munir Iqbal; Osbourne Quaye